2015
DOI: 10.1002/cncr.29503
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 trial of sunitinib and gemcitabine in patients with sarcomatoid and/or poor‐risk metastatic renal cell carcinoma

Abstract: BACKGROUND: Sarcomatoid renal cell carcinoma (RCC) is associated with an aggressive biology and a poor prognosis. Poorrisk RCC is defined by clinical prognostic factors and demonstrates similarly aggressive behavior. No standard treatment exists for patients with sarcomatoid RCC, and treatment options for patients with poor-risk disease are of limited benefit. The objective of this study was to investigate the efficacy of antiangiogenic therapy in combination with cytotoxic chemotherapy in clinically aggressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 28 publications
3
40
0
3
Order By: Relevance
“…[186][187][188][189][190][191] The potential role of sunitinib in combination gemcitabine has been investigated in a phase II trial of RCC with sarcomatoid features. 192 Results show that the combination is well tolerated and active, especially in patients with rapidly progressing disease. 192 Ongoing trials are studying sunitinib in combination with gemcitabine compared with sunitinib alone in patients with sarcomatoid features (ClinicalTrials.…”
Section: Chemotherapy For Metastatic Rccmentioning
confidence: 94%
See 1 more Smart Citation
“…[186][187][188][189][190][191] The potential role of sunitinib in combination gemcitabine has been investigated in a phase II trial of RCC with sarcomatoid features. 192 Results show that the combination is well tolerated and active, especially in patients with rapidly progressing disease. 192 Ongoing trials are studying sunitinib in combination with gemcitabine compared with sunitinib alone in patients with sarcomatoid features (ClinicalTrials.…”
Section: Chemotherapy For Metastatic Rccmentioning
confidence: 94%
“…192 Results show that the combination is well tolerated and active, especially in patients with rapidly progressing disease. 192 Ongoing trials are studying sunitinib in combination with gemcitabine compared with sunitinib alone in patients with sarcomatoid features (ClinicalTrials. gov identifier: NCT01164228).…”
Section: Chemotherapy For Metastatic Rccmentioning
confidence: 94%
“…Relatively less is known about these rare kidney cancer subtypes. Collecting duct carcinomas were recognized as a distinct clinical diagnosis in the 1980s and are characterized by a tubulopapillary pattern and desmoplastic stroma; in some cases, they are difficult to distinguish histologically from urothelial carcinomas. However, biologically, they may be very different from urothelial carcinomas, because the 2 cancers contain very different patterns of chromosomal gain and loss .…”
Section: The Evolution Of Rcc Subclassification: a Path Of “Splitting”mentioning
confidence: 99%
“…Michaelson et al (2015) reported a phase 2 study of the combination of gemcitabine with sunitinib in patients poor-risk features, including patients with sarcomatoid histology the combination was tolerated and showed some activity and is currently being evaluated in a randomised study (Clinicaltrials.gov, NCT01164228).…”
Section: Combination Therapymentioning
confidence: 99%